Determinants of Stunting among Children Aged 0–24 Months: A Cross-Sectional Study - Nisa, Hainun; Kresnawati, Puri; rostianingsih, Dewi; Junita, Friska (Chakra Brahmanda Lentera Institute, 2025)
Background: This study was conducted in response to the issue of stunting in Bekasi Regency, which had remained at a stagnant rate of 21.5%. Therefore, the local government aimed to continue reducing this figure to 4%. The purpose of this study was to determine the determinants of stunting in children aged 0-24 months. Methods: This study used analytical observation with a cross-sectional approach. The population of mothers who had children aged 0-24 months was 156 respondents, accidental sampling technique, with a sample size of 61 respondents, independent variables were history of Chronic Energy Deficiency (CED) pregnancy using medical record of MUAC (Mid-Upper Arm Circumference), using a questionnaire to exclusive breastfeeding, maternal education, age of pregnant women, and using Maternal and Child Health books (MCH books) to immunization historys and dependent variable are stunting using Maternal and Child Health books (MCH books). Results: It is known that the Chronic Energy Deficiency (CED) significance value is 0.009, exclusive breastfeeding is 0.006, maternal age is 0.0141, and immunization history is 0.005. Thus, the four factors have a p-value <0.05. At the same time, the significance value of maternal education is 0.358 > 0.05. Based on the results of the Odds Ratio (OR) CED obtained, 20.889, exclusive breastfeeding 19.500, and maternal age 15.300, which indicates that CED has a higher chance of affecting the incidence of stunting in children aged 0-24 months compared to other variables. Conclusion: The community should be able to take preventive steps to provide nutrition, ensuring that the fetus or baby born does not experience stunting.